2014
DOI: 10.1177/0017896914556907
|View full text |Cite
|
Sign up to set email alerts
|

Teacher experiences of delivering an obesity prevention programme (The WAVES study intervention) in a primary school setting

Abstract: Objective: There has been a wealth of childhood obesity prevention studies in school-based settings. However, few have investigated the experiences of school staff charged with delivery of such programmes. This study aimed to elicit teachers’ experiences of delivering a childhood obesity prevention programme for children aged 6–7 years. Design: Descriptive-interpretive qualitative study. Setting: Primary schools participating in the UK West Midlands ActiVe lifestyle and healthy Eating in School children (WAVES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 28 publications
(29 reference statements)
3
31
0
Order By: Relevance
“…Process evaluation —detailed results from the process evaluation are reported separately. 17 18 19 Briefly, the intervention was generally well implemented, although no school delivered all components completely as intended. The scores developed to represent overall fidelity of programme implementation show that just under half the schools (12/26) achieved at least 75% of the maximum possible score and only five schools failed to achieve at least 65% of that maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Process evaluation —detailed results from the process evaluation are reported separately. 17 18 19 Briefly, the intervention was generally well implemented, although no school delivered all components completely as intended. The scores developed to represent overall fidelity of programme implementation show that just under half the schools (12/26) achieved at least 75% of the maximum possible score and only five schools failed to achieve at least 65% of that maximum.…”
Section: Resultsmentioning
confidence: 99%
“…Our experience of working with UK schools suggested that teachers are overburdened and schools are regularly approached to take part in projects and initiatives. 55 There are similarities between Australia and the UK in the proportion of men who are overweight or living with obesity. 5,56 Australian guidance for adult fruit and vegetable intake is five or six portions each day, whereas the UK's guidance is five portions.…”
Section: Helping Dad Stay On Trackmentioning
confidence: 99%
“…From a PE pedagogy perspective, past research raised concerns that parents did not always perceive PE as valuable in PA promotion [36]. Gaining parents support has been also perceived as a key challenge by PE teachers to ensure consistency of messages between home and school [37]. Among the barriers that hinder adequate collaboration, a lack of parental knowledge and understanding of healthy lifestyle practices has been highlighted [37,38].…”
Section: Introductionmentioning
confidence: 99%